Genotypic Variation in Nitrogen Use-Efficiency Traits of 28 Tobacco Genotypes - André B. Andrade (Agronomy, 2020)
Knowing the nitrogen use efficiency (NUE) of crops is crucial to minimize environmental pollution, although NUE is rarely provided for numerous genotypes in the tobacco (Nicotiana tabacum L.) crop. Through the growth of contrasting genotypes in nutritive solutions, we aimed to characterize five NUE components of 28 genotypes and to classify them according to their efficiency and responsiveness to nitrogen (N) availability. On average, physiological N use efficiency, N harvest index, and N uptake efficiency decreased by 16%, 4%, and 57%, respectively, under N-deficient conditions, while N utilization efficiency decreased by 43% at adequate N supply. The relative efficiency of N use varied from 35% to 59% among genotypes. All genotypes of the Virginia and Maryland varietal groups were efficient, and those of the Burley, Comum, and Dark groups were inefficient, while the responsiveness varied among genotypes within varietal groups, except for Maryland genotypes. Our findings are helpful in indicating genotypes with distinguished efficiency and responsiveness to N supply, which can be further chosen according to soil N level or affordability to N fertilizers worldwide in tobacco crops. In a general framework, this can lead to a more sustainable use of N and can support tobacco breeding programs for NUE.